Impairment of interrelated iron- and copper homeostatic mechanisms in brain contributes to the pathogenesis of neurodegenerative disorders - Tina eSkjørringe; Tina eSkjørringe; Lisbeth Birk Møller; Torben eMoos (Frontiers Media S.A., 2012)
Iron and copper are important co-factors for a number of enzymes in the brain, including enzymes involved in neurotransmitter synthesis and myelin formation. Both shortage and an excess of iron or copper will affect the brain. The transport of iron and copper into the brain from the circulation is strictly regulated, and concordantly protective barriers i.e. the blood-brain barrier (BBB) and the blood-cerebrospinal fluid (CSF) barrier (BCB) have evolved to separate the brain environment from the circulation. The uptake mechanisms of the two metals interact. Both iron deficiency and overload lead to altered copper homeostasis in the brain. Similarly, changes in dietary copper affect the brain-iron homeostasis. Moreover, the uptake routes of iron and copper overlap each other which affect the interplay between the concentrations of the two metals in the brain. The divalent metal transporter-1 (DMT1) is involved in the uptake of both iron and copper. Furthermore, copper is an essential co-factor in numerous proteins that are vital for iron homeostasis and affects the binding of iron-response proteins to iron-response elements in the mRNA of the transferrin receptor, DMT1 and ferroportin, all highly involved in iron transport. Iron and copper are mainly taken up at the BBB, but the BCB also plays a vital role in the homeostasis of the two metals, in terms of sequestering, uptake and efflux of iron and copper from the brain. Inside the brain, iron and copper are taken up by neurons and glia cells that express various transporters